2008
DOI: 10.3174/ajnr.a1278
|View full text |Cite
|
Sign up to set email alerts
|

Brain Stem Diffusion-Weighted Imaging Lesion Score: A Potential Marker of Outcome in Acute Basilar Artery Occlusion

Abstract: BACKGROUND AND PURPOSE:The benefit of recanalization in basilar artery occlusion (BAO) has been established. The baseline extent of brain stem damage may also influence the outcome. We investigated whether a baseline diffusion-weighted imaging (DWI) score may provide additional prognostic value in BAO.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
62
0
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(68 citation statements)
references
References 22 publications
2
62
0
3
Order By: Relevance
“…18 More recently, authors [15][16][17] have studied patients with a posterior circulation stroke by using various neuroradiologic scales of DWI. In 2010, Tei et al 17 evaluated the usefulness of the pc-ASPECTS on DWI to predict functional outcome in 132 patients with a posterior circulation infarction.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…18 More recently, authors [15][16][17] have studied patients with a posterior circulation stroke by using various neuroradiologic scales of DWI. In 2010, Tei et al 17 evaluated the usefulness of the pc-ASPECTS on DWI to predict functional outcome in 132 patients with a posterior circulation infarction.…”
Section: Discussionmentioning
confidence: 99%
“…Using a 10-point semiquantitative DWI score, they found that in univariate analyses, all patients with a lesion score of Ͼ3 had a worse outcome or died (P ϭ .026). Cho et al 16 analyzed 29 patients treated with endovascular procedures for ABAO and found that the brain stem score was the only independent baseline predictor of clinical outcome. In contrast to previous studies 13, 14 on vertebrobasilar ischemic stroke, they found a significant association between the DWI brain stem lesion score and the baseline NIHSS score, as well as between the presence and length of a coma before treatment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Однако изолированная окклюзия ВСА (без вовлечения пе-редней хориоидальной артерии) независимо ассо-циирована с БФИ [56][57][58][59][60][61]. Установлено, что шкалы BASIS и CBS превосходят ASPECTS в отношении прогнозирования ФИ, при этом CBS имеет боль-шую чувствительность, а BASIS -специфичность [62][63][64][65]. ФИ напрямую коррелирует как со степе-нью коллатерального кровотока, так и реканализа-цией артерий, так как от них напрямую зависит КОИ [66][67][68][69][70].…”
Section: предикторы фи оии основанные на оценке состояния паренхимы unclassified